Farmland Birds and their Importance in Agro ecosystem: A Review - Parajuli, Kanchan; Ghimire, Pranish (International Research Journal of MMC, 2024)
Avian fauna provide a variety of functions, including predators, pollinators, scavengers, seed dispersers, pests controller, nutrient cycling, ecosystem engineers, and many others. Birds play important ecological and economic functions however they are sometimes overlooked simply because of a lack of knowledge. However, as bird populations drop globally, so do the ecological advantages given by these species. To support bird conservation, this review study focuses on the role of birds in the agro-ecosystem and their benefits to humans. Biodiversity databases and existing literature were reviewed to establish baseline information on farmland bird species and their preferences. Searches were limited to articles published between 2005 to 2024. Healthy bird populations and habitats would help to safeguard a variety of ecological functions, ultimately benefiting human health. Farmland birds are disappearing. Due to the widespread use of pesticides, lack of habitat, birds and other animals are disappearing and unnecessary harmful pest species are increasing and the agricultural environment is deteriorating. So, this review paper tries to emphasize on urgent conservation measures that are necessary for the protection of agricultural birds which are essential for the health of both natural and agricultural environments.